2009
DOI: 10.4103/0255-0857.53206
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Nasopharyngeal Culture in Identification of Pathogen in Middle Ear Fluid in Chronic Otitis Media With Effusion

Abstract: PCR is a more reliable method to detect middle ear pathogens in MEF in comparison with the conventional culture methods. The NP colonization wasn't found to be an indicator of the pathogen in MEF although middle ear pathogens colonize more in nasopharynx of diseased children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 22 publications
2
8
0
1
Order By: Relevance
“…Some studies have suggested a good agreement for serotypes and susceptibility patterns of microorganisms found in paired NP and MEF samples, suggesting that NP sampling may be of value for the monitoring of antimicrobial resistance in children with OM. 10,12,23 Last, only 4 studies used polymerase chain reaction: these detected more microorganisms in AOM and OME than conventional methods except for the study by Eser et al 11 None used newer molecular techniques that could even provide higher accuracy in testing for microbial presence. 34,35 For a better understanding of the etiology of OM and the relation between the microflora in the nasopharynx and the middle ear, more research into microbial interactions and pathogen-host interactions is needed using more advanced diagnostic techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have suggested a good agreement for serotypes and susceptibility patterns of microorganisms found in paired NP and MEF samples, suggesting that NP sampling may be of value for the monitoring of antimicrobial resistance in children with OM. 10,12,23 Last, only 4 studies used polymerase chain reaction: these detected more microorganisms in AOM and OME than conventional methods except for the study by Eser et al 11 None used newer molecular techniques that could even provide higher accuracy in testing for microbial presence. 34,35 For a better understanding of the etiology of OM and the relation between the microflora in the nasopharynx and the middle ear, more research into microbial interactions and pathogen-host interactions is needed using more advanced diagnostic techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it can result in developmental impairment of linguistic, behavioral, motor and social skills (1, 11, 12). …”
Section: Discussionmentioning
confidence: 99%
“…In our study the conventional culture and API identification revealed 30 CNS species (30.9%), with S. epidermidis as the leading species of CNS in the tested groups of patients. The detection rate of middle-ear pathogens in chronic infections, with conventional culture methods, varies between 2 and 20% for bacterial pathogens [13,17]. In many cases, is not satisfactorily in chronic OME.…”
Section: Discussionmentioning
confidence: 99%